Evaluation of modified used engine oil acting as a dispersant for concentrated coal–water slurry. (1st July 2016) - Zhang, Kang; Jin, Li'e; Cao, Qing
Highlights: A new disposal and updated way for used engine oil (UEO) were provided. SUEO synthesized through sulfonation of UEO exhibited surfactant properties. SUEO performed better than two commercial dispersants in coal–water slurry. The stability of CWS prepared by SUEO was better than that of CWS with others. The tight water film outside of coal was ascribed to different carbon chains of SUEO. Abstract: In order to convert the used engine oil (UEO) to a fine chemicals, the properties of engine oil (EO) and UEO were initially compared by FTIR, 1 H NMR, and thermal behavior analyses. The UEO composition was first modified by sulfonation and then separated through separating funnel. Results showed that the as-prepared product, sulfonated UEO (SUEO), exhibits the properties of a surfactant. The surface tension of the aqueous SUEO solution was 34.64 mN m −1 at the critical micellar concentration of 3.02 g L −1, which was one half of 72.27 mN m −1 of distilled water. Up to 0.3 wt.% SUEO was used as a dispersant for coal–water slurry (CWS), and the viscosity of CWS was 170 mPa s when the content of coal powder was 65 wt.% at shear rate of 100 s −1, and the rheological behavior belonged to pseudoplastic fluids. Experiments on the stability of CWS containing 0.3 wt.% SUEO demonstrated that the penetration ratio reached 37.8% after 15 days, which was higher by 12.1% than that of CWS without dispersant. Compared with commercial dispersants sodium lignosulfonate and sodium dodecyl sulfate, SUEO displayed a good performance for either liquidity or stability of CWS. In addition, the possible reason for the excellent behavior of CWS prepared with SUEO was discussed. Overall, this study provided a new disposal and updated way for UEO.